Closing the emission price gap. (March 2015) - Edenhofer, Ottmar; Jakob, Michael; Creutzig, Felix; Flachsland, Christian; Fuss, Sabine; Kowarsch, Martin; Lessmann, Kai; Mattauch, Linus; Siegmeier, Jan; Steckel, Jan Christoph
Highlights: There are important unilateral incentives for emission pricing. These include public finance, domestic climate impacts and co-benefits. Different countries face different incentives for emission pricing. Unilateral emission pricing could provide a basis for a hybrid climate agreement. Countries would then negotiate policy packages rather than emission targets. Abstract: Even without internationally concerted action on climate change mitigation, there are important incentives for countries to put a price on their domestic emissions, including public finance considerations, internalizing the climate impacts of their own emissions, and co-benefits, such as clean air or energy security. Whereas these arguments have been mostly discussed in separate strands of literature, this article carries out a synthesis that exemplifies how policies to put a price on emissions can be conceptualized in a multi-objective framework. Despite considerable uncertainty, empirical evidence suggests that different countries may face quite different incentives for emission pricing. For instance, avoided climate damages and co-benefits of reduced air pollution appear to be the main motivation for emission pricing in China, while for the US generating public revenue dominates and for the EU all three motivations are of intermediate importance. We finally argue that such unilateral incentives could form the basis for incremental progress in international climate negotiations toward a realistic climate treaty based on national interest and differentiated emission pricing and describe how such an agreement could be put into practice.